Fluorescent Cadmium Chalcogenide Nanoclusters in Ubiquitin. Issue 2 (30th December 2020) - Akyüz, Özlem; Scheffner, Martin; Cölfen, Helmut
Abstract : Fluorescent semiconductor nanoclusters (FNCs) have received much attention by many scientists due to their attractive functions and features. However, the traditional organometallic chemical synthesis routes for such FNCs require harsh reaction conditions in organic solvents, which limit their use in biological applications. Therefore, developing synthesis strategies for the fabrication of FNCs by association with proteins under mild reaction conditions is pivotal to improve their functionalities. In addition, understanding the effect of structural and chemical properties of proteins on the synthesis mechanism of FNCs is one of the key points, which eventually enables to control and tune the photophysical properties of FNCs. The purpose of this study is to introduce the syntheses of cadmium selenide nanocluster (CdSeNC) and cadmium sulfide nanocluster (CdSNC) by using ubiquitin, a small cysteine‐free protein, and investigating their properties via spectroscopic and microscopic methods. It is shown that significant changes in the protein structure as well as in its oligomerization occur upon the formation of the highly hydrated FNCs. Abstract : The synthesis of semiconductor nanoclusters (NCs) under ambient conditions attracts great interest from many scientists to decrease the negative effects in their applications. Therefore, proteins take role in incorporating and stabilizing NCs under mild reaction conditions. Ubiquitin, which is a small and cysteine‐free protein, is capable to interact and stabilize fluorescent cadmium chalcogenide NCs by forming mostly oligomeric species.